Measurement of Ultra-Short Solitary Electromagnetic Pulses - Eva Gescheidtova; Miloslav Steinbauer; Pavel Fiala (Advances in Electrical and Electronic Engineering, 2004)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">In connection with the events of the last few years and with the increased number of terrorist activities, the problem of identification and measurement of electromagnetic weapons or other systems impact occurred. Among these are also microwave sources, which can reach extensive peak power of up to Pmax = 100 MW. Solitary, in some cases several times repeated, impulses lasting from tp E <1, 60>ns, cause the destruction of semiconductor junctions. These days we can find scarcely no human activity, where semiconductor structures are not used. The problem of security support of the air traffic, transportation, computer nets, banks, national strategic data canter’s, and other applications crops up. Several types of system protection from the ultra-short electromagnetic pulses present itself, passive and active protection. The analysis of the possible measuring methods, convenient for the identification and measurement of the ultra-short solitary electromagnetic pulses in presented in this paper; some of the methods were chosen and used for practical measurement. This work is part of Research object MSM262200022 "Research of microelectronic systems".